PERFORMA TEMPERATUR DAN KELEMBAPAN UDARA PADA OBJEK WISATA HAWAI WATERPARK MALANG - Krisma, Agatha; Ar. Wasiska Iyati, ST., MT., IAI (Jurnal Mahasiswa Departemen Arsitektur, 2024)
Hawai Waterpark Malang is a popular water tourism destination in Malang City, East Java. The tropical atmosphere, designed to be refreshing, and various water attractions can attract visitors. The design and layout of facilities, including the placement of shaded areas, can significantly impact the thermal comfort of visitors. Although many studies have been conducted on thermal comfort in water parks, research specifically focusing on local conditions like Malang's tropical climate is still limited. This study employs a research method using the WGBT Meter as an instrument and data analysis using the Temperature Humidity Index formula. Based on the research conducted at Hawai Waterpark Malang, it can be concluded that the performance of temperature and humidity at Hawai Waterpark Malang has a "partially uncomfortable" and "uncomfortable" index value Keywords: abstract, summary